The effectiveness of in-game advertising in mobile games - S. Klose; N. A. Truong (Research Journal for Applied Management (RJAM), 2022)
Purpose: This study aims to investigate the effectiveness of branding through mobile games with ingame advertising (IGA). The concept of in-game advertising will be linked with game experience, game engagement, brand attitude, and brand equity to demonstrate its effectiveness empirically. Design/Methodology/Approach: An online survey is conducted to help collect attitudinal responses of gamers about the collaboration between a mobile game and a beverage brand. The conclusion is drawn based on hypotheses testing using the Partial Least Squares Structural Equation Modeling (PLSSEM) technique. Findings: The results show that in-game advertising positively influences player experience and game engagement of players as well as brand attitude and brand equity. Further, brand attitude plays an important mediating role in the relationship between in-game advertising and brand equity. Research implications: In-game advertising is a potential alternative to traditional media. For game publishers, in-game advertising can help improve player retention by enhancing the enjoyment, hedonism, and realism of their gameplays. For brands, in-game advertising possibly improves brand equity by positively influence people's attitude towards the brand. Limitations/Future research: The research contains some limitations regarding the scope of the study, stimuli selections, and sample size. Researchers can consider some possible directions for their future research about in-game advertising, such as examining its influence on gamers' behaviors, investigating its influence in different contexts or on different perspectives. Originality/Value: The results of this study provide answers to the undiscovered effectiveness of ingame advertising in mobile game contexts. Thus, it makes a significant contribution to the holistic picture of advertising in digital games.umentenvertrauen
Keywords: 650; in-game advertising; iga; mobile games; consumer-based brand equity; brand equity; game experience; game engagement